Reappraising host cellular factors involved in attachment and entry to develop antiviral strategies against porcine reproductive and respiratory syndrome virus - Li, Rui; Qiao, Songlin; Zhang, Gaiping (Frontiers in Microbiology, 2022)
Porcine reproductive and respiratory syndrome (PRRS), caused by PRRS virus (PRRSV), is a highly contagious disease that brings tremendous economic losses to the global swine industry. As an intracellular obligate pathogen, PRRSV infects specific host cells to complete its replication cycle. PRRSV attachment to and entry into host cells are the first steps to initiate the replication cycle and involve multiple host cellular factors. In this review, we recapitulated recent advances on host cellular factors involved in PRRSV attachment and entry, and reappraised their functions in these two stages, which will deepen the understanding of PRRSV infection and provide insights to develop promising antiviral strategies against the virus.